PROMOTING SKILL OF SPEAKING VIA TWO STAY TWO STRAY STRATEGY AMONG THE ENGLISH STUDENTS OF FKIP OF BENGKULU UNIVERSITY - Kasmaini Kasmaini; Riswanto Riswanto (Proceedings of ISELT FBS Universitas Negeri Padang, 2017)
The study is aimed at describing the effectiveness of two stay and two stray in enhancing  students’ speaking ability. The paper is derived from the research result conducted among the 35 English department students of FKIP of University of Bengkulu. Classroom action research design with 3 cycles was applied to encourage students’ speaking skill. Observation checklist, fieldnote and speaking test instruments were used to capture students’ progress (reflection and evaluation) . Observation was done to see how well the strategy was understood and implemented by the students. Fieldnote aimed at jotting down success and constraints of the strategy usage and tes instrument was administered to evaluate the grading and scoring development during the first, second and third cycles. Reflecting and evaluating were conducted at the end of every cycle. Based on observation and fieldnote that the students’participation were getting increased in every cycle. Besides, the average score and grade at the end of 3 cycles were getting improved. Mean score of cycle 1 was 59.00, cycle 2 was 65.00 and final cycle was 72.00. It can be concluded that two stay and two stray strategy boosted speaking ability for English department students of FKIP of Bengkulu University.